Effects of 12-Month Training Intervention on Physical Fitness, Body Composition, and Health Markers in Finnish Navy Soldiers - Myllylä Mikko; Parkkola Kai I; Ojanen Tommi; Heinonen Olli J; Ruohola Juha-Petri; Vahlberg Tero; Kyröläinen Heikki (Switzerland, 2025)
Background: Most Western adults do not meet the recommendations for sufficient activity, and obesity is a global problem. Similar trends are also seen among Western military personnel. Many successful physical training interventions have been carried out in military environments, but the interventions have been quite short term, and the training has been supervised. Therefore, the aim of this study was to investigate the effects of a 12-month voluntary motivational training intervention among the Finnish Defence Forces' (FDF) Navy soldiers.
Methods: In total, 77 FDF Navy soldiers, serving in missile patrol boats, took part in the study. The intervention group (IG) contained 45 participants and the control group (CG) contained 32 participants. The IG was divided into four teams that carried out the intervention, while the CG took part in only the measurements.
Results: Most of the participants (65%) in the IG reported that they had increased their exercise volume during the intervention, but no major beneficial impacts on the physical fitness, body composition, or health markers were observed. Nevertheless, there was a clear diversity visible between the subgroups in the IG. The team that reported the most exercise had the best motivation and the most motivated team coach and also had the most improved physical fitness and body composition results.
Conclusions: The present study points out that in military environments, long-term voluntary training interventions may not be as successful as short-term supervised interventions. The results also suggest that in voluntary training interventions among military personnel, the participants' motivation to exercise is a key factor when improving physical fitness.